Interactive E-Modules with Cases of Local Wisdom in Learning Animal Diversity to Improve Student Learning Outcomes - Winangun, I Made Ari (Universitas Pendidikan Ganesha, 2024)
E-modules and other learning resources are still limited in the form of softcopy and film packaging so they are less interactive. Therefore, interactive e-modules as a learning resource with cases of local wisdom to facilitate the student learning process, especially on Animal Diversity material are needed. This study aims to analyze the effectiveness of interactive e-modules accompanied by cases of local wisdom in improving student learning outcomes. This research is the implementation stage in the research and development of the ADDIE model which is carried out with a one-group pretest-posttest design. The subjects in this study were 60 PGSD Study Program students. The instrument in this study is a test of learning outcomes on Animal Diversity learning material. Data collection techniques are carried out before the implementation of interactive e-modules (pretest) and after the implementation of interactive e-modules (posttest). Data analysis was carried out descriptively to obtain an overview of learning outcomes before and after the application of interactive e-modules and was carried out inferentially with t and N-gain tests. The results of this study show that interactive e-modules with cases of local wisdom are quite effective in improving student learning outcomes in the subject of Animal Diversity. The implication of this research is that interactive e-modules with local wisdom cases are effective in improving student learning outcomes on Animal Diversity material, showing the potential for the use of more interactive learning resources in learning. It was concluded that interactive e-modules with cases of local wisdom can improve student learning outcomes.